What Drives Opposition to Economic Reforms? The Role of Ex Ante Uncertainty. (September 2018) - Potter, Alan
The theoretical literature on support for pro-market economic reforms identifies uncertainty about the future consequences of reform as an important determinant of opposition to pro-market policies. However, this literature does not rigorously test the role of uncertainty on support for pro-market reforms. This paper addresses this gap by testing the role of uncertainty using a new geocoded dataset of state-owned enterprises in India and a difference-in-differences strategy. I find that voters who are threatened with privatization but do not experience the policy vote against the privatizing party whereas voters that actually experience privatization vote in favor of the privatizing party. These results provide strong empirical support for the role of uncertainty to explain opposition to economic reform programs.